2006
DOI: 10.1177/0363546505282626
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Endoscopic Anterior Cruciate Ligament Reconstruction with Patellar Tendon Autograft

Abstract: Endoscopic anterior cruciate ligament reconstruction with patellar tendon autograft affords and maintains good self-reported assessments and clinical ligament evaluation up to 13 years. Radiographic degenerative changes were seen in three quarters of patients. Almost half developed loss of extension, suggesting onset of early osteoarthritis. Patients who had undergone meniscectomy at the time of reconstruction had increased clinical ligament laxity over time and greater odds of graft rupture, possibly reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
191
6

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(208 citation statements)
references
References 35 publications
11
191
6
Order By: Relevance
“…In contrast to their report and other previously published investigations the mean Lysholm score was lower in both of our treatment cohorts. While Salmon et al [11] showed good to excellent Lysholm knee scores in 80% of their patients, with a mean score of 89 points after 13 years of follow-up undergoing endoscopic ACL reconstruction, the present Lysholm mean was 68 points for our ACL reconstructed patients.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…In contrast to their report and other previously published investigations the mean Lysholm score was lower in both of our treatment cohorts. While Salmon et al [11] showed good to excellent Lysholm knee scores in 80% of their patients, with a mean score of 89 points after 13 years of follow-up undergoing endoscopic ACL reconstruction, the present Lysholm mean was 68 points for our ACL reconstructed patients.…”
Section: Discussioncontrasting
confidence: 61%
“…Kostogiannis et al [14] reported good functional scores in their conservatively-treated patients at the 15 year follow-up. As a large number of studies have reported on clinical assessment after ACL insufficiency but only few extend beyond ten years of follow-up [13], we can just speculate on a potential influence of time as there is certain evidence of a significant deterioration of the clinical scores over time [11,12]. Interestingly, the self-reported activity level graded according to Tegner had a mean of 4 for ACL and 5 for non-ACL and was therefore higher than in comparable studies [11,12].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Long-term studies have reported a high incidence of joint degeneration (as much as 52% to 56% 12 to 13 years after surgery) [36,42] and an estimated 8% to 10% of ACL reconstructions result in recurrent instability and graft failure [18,23,51]. Furthermore, studies have suggested that the ability of current reconstruction techniques to prevent degenerative changes compared with nonoperative treatment is limited [11,[13][14][15]36].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Furthermore, recent long-term data following reconstruction with a PT autograft showed osteoarthritic changes in 79% of patients. 11 It is also well known that the biomechanical properties of the healing PT are substantially inferior when compared to normal tissues. [12][13][14][15] Therefore, there is a need to enhance the healing of the PT while limiting the fat pad adhesion in some patients to help to improve the function of the healing PT and restore the normal extensor mechanism of the knee following ACL reconstruction.…”
Section: Introductionmentioning
confidence: 99%